Penser en français - Cristina Robalo Cordeiro (Carnets)
Trying to grasp the specificity of the French language, it may be useful to forget for a moment the numbers and spaces which determine its quantitative dimension and to concentrate on the speaking Subject. In a comparison with the Portuguese, we describe here what it means 1. to think while speaking, 2. to think while reading, 3. to think while writing… in French.